Interface Theories for (A)synchronously Communicating Modal I/O-Transition Systems - Sebastian S. Bauer; Rolf Hennicker; Stephan Janisch (Electronic Proceedings in Theoretical Computer Science, 2011)
Interface specifications play an important role in component-based software development. An interface theory is a formal framework supporting composition, refinement and compatibility of interface specifications. We present different interface theories which use modal I/O-transition systems as their underlying domain for interface specifications: synchronous interface theories, which employ a synchronous communication schema, as well as a novel interface theory for asynchronous communication where components communicate via FIFO-buffers.